Associations of multimorbidity on frailty and dependence among an elderly rural population: Findings from the AHSETS study. (December 2020) - Kshatri, Jaya Singh; Palo, Subrata Kumar; Bhoi, Trilochan; Barik, Shakti Ranjan; Pati, Sanghamitra
Highlights: The prevalence of multimorbidity is high (48.8 %) among the rural elderly population in eastern India. The prevalence of frailty was also high (58.6 %) and dependence for activities of daily living is significant (5.4 %). Frailty and dependence increased with increasing age, while age beyond 60 years had no effect on the multimorbidity status. There is significant association between multimorbidity and increased risk of frailty. There was no significant association between dependency and number of chronic diseases when adjusting other variables. Abstract: This cross-sectional study was conducted among a rural elderly population of 725 individuals aged over 60 years from Eastern India to assess the association of multiple chronic diseases with frailty and dependence. Multimorbidity, frailty, and dependence were assessed using prevalidated tools. Regression models were used to assess the association between variables and adjust for confounders. The overall prevalence of multimorbidity was 48.8 % and that of frailty and dependence for activities of daily living was 58.6 % and 5.4 %, respectively. There was no statistically significant difference (p = 0.53) between the mean age of persons with and without multimorbidity. Frailty and dependency, however, showed a significant increasing trend with the mean age. Unadjusted bivariate analyses showed a significantly larger proportion of persons who were frail or at risk of frailty having multimorbidity as compared to those who were robust. Logistic regression models showed a significant association between risk of frailty and multimorbidity but failed to demonstrate a significant relationship between dependency and number of chronic diseases when adjusted for the interaction between frailty and chronic diseases. There was a significant association between dependence, frailty, and multimorbidity. Further research to determine the extent, direction, and nature of this complex relationship needs to be explored.